The Impact of Limited Prosthetic Socket Documentation: A Researcher Perspective - Olsen, Jennifer; Turner, Shruti; Chadwell, Alix; Dickinson, Alex; Ostler, Chantel; Armitage, Lucy; McGregor, Alison H.; Dupan, Sigrid; Day, Sarah (Frontiers in Rehabilitation Sciences, 2022)
The majority of limb prostheses are socket mounted. For these devices, the socket is essential for adequate prosthetic suspension, comfort and control. The socket is unique among prosthetic components as it is not usually mass-produced and must instead be custom-made for individual residual limbs by a prosthetist. The knowledge of what constitutes ‘good’ socket fit is gained by expert prosthetists and technicians over years of experience, and rarely documented. The reliance on tacit knowledge makes it difficult to standardise the criteria for a well-fitting socket, leading to difficulties understanding the impact of socket fit. Despite its importance, the workflow for socket fitting is often overlooked in literature. Due to the customised nature of sockets, if information is provided in literature, generally only the type of socket and suspension mechanism is noted, with information regarding the fitting and manufacturing processes omitted. In this paper, the concerns, issues and consequences arising from lack of upper and lower limb socket documentation are discussed from a researcher perspective, supported by healthcare professionals and socket fabrication specialists. Key changes are proposed to the way socket manufacturing and evaluation are documented to assist future research.